2014
DOI: 10.2478/folmed-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Diagnosis of Intramural Hematoma in The Colon sigmoideum In a Child With High Titer Inhibitory Hemophilia A

Abstract: Lower gastrointestinal bleeding is a rare condition in childhood pathology. The incidence of this disorder in the general population of Bulgarian children is unknown. We report a case of a 7-year-old child with diagnosed hemophilia A and high titer of factor VIII inhibitor; the patient was admitted into the Department of Pediatrics and Medical Genetics for rectorrhagia after falling onto his buttocks while playing. Colonoscopy showed submucosal hematoma 25 cm from the anocutaneous line occluding the intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…A postpolypectomy bleeding incidence of 31% was observed in a case series of mostly severe and moderate haemophilia A and haemophilia B patients . Gastrointestinal intramural haematomas have been reported after upper and lower endoscopy in haemophilia A and haemophilia B . Additionally, one study reported two bleeding events postendoscopic variceal ligation in nine procedures for patients with severe haemophilia A and HCV cirrhosis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A postpolypectomy bleeding incidence of 31% was observed in a case series of mostly severe and moderate haemophilia A and haemophilia B patients . Gastrointestinal intramural haematomas have been reported after upper and lower endoscopy in haemophilia A and haemophilia B . Additionally, one study reported two bleeding events postendoscopic variceal ligation in nine procedures for patients with severe haemophilia A and HCV cirrhosis …”
Section: Introductionmentioning
confidence: 99%
“…12 Gastrointestinal intramural haematomas have been reported after upper and lower endoscopy in haemophilia A and haemophilia B. 13,14 Additionally, one study reported two bleeding events postendoscopic variceal ligation in nine procedures for patients with severe haemophilia A and HCV cirrhosis. 16 For patients with VWD, guidelines from the National Heart, Lung, and Blood Institute suggest that patients undergoing endoscopy without biopsy be treated with a single von Willebrand factor (VWF) treatment pre-endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic cases, with unknown or uncertain origin, have also been described but their occurrence has been reported in less than 5% of cases [2,8,[15], [16], [17], [18], [19], [20]]. Intramural hematoma may occur from esophagus to rectum [17], being the duodenum the most common site [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic imaging may be misleading [6]. Furthermore, there is little information about the appropriate treatment, which has been either non-operative or surgical in the rare cases reported in the Literature [[6], [7], [8]]. We report a unique case of right colon intramural hematoma of unknown etiology, with an atypical clinical presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Colonic intramural hematoma is an uncommon complication of diagnostic colonoscopy, with only a handful of reported cases (2–4). Colonic hematomas have been reported in children secondary to accidental and nonaccidental trauma, bleeding disorders, and anticoagulant therapy (5–8). This is one of the first reported case of colonic hematoma complicating diagnostic colonoscopy in a pediatric patient.…”
Section: Figurementioning
confidence: 99%